Influencing Factors of Audience's Willingness to Consume of Outdoor Music Festival Based on Grounded Theory - Panqiang Niu; Zetong Li; Anang Masduki (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
This paper adopts grounded theory to conduct an exploratory study on the influencing factors of outdoor music festival audience's willingness to consume. First, we used 'music festival' as the search keyword to collect secondary information such as blog posts, online pictures, and news reports related to outdoor music festivals. Then, based on the previous research and the author's experience, this paper conducted ten one-on-one in-depth interviews and a group interview with the Nanjing Forest Music Festival in China as the field research object. On this basis, the article performed word frequency analysis and semantic network analysis on the text data and obtained keywords with high frequency and the core words in focus. Finally, according to the triple coding results of the grounded theory, combined with the cognitive mediation model, a model of influencing factors of the audience's willingness to consume in outdoor music festivals is constructed